Work discipline as the main determinant of employee performance: the role of competence, motivation, and job satisfaction in public service organizations - Anggita Savitri; Suhardi Suhardi; Hamdan Hamdan (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to analyze the influence of competence, work discipline, and motivation on employee performance with job satisfaction as a mediating variable at the Pangkalpinang Class I Immigration Office. The study used a quantitative approach with the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS). The research sample consisted of 80 respondents taken using a saturated sampling technique. Data were collected through a Likert scale questionnaire and analyzed using SmartPLS. The results showed that work discipline had a positive and significant effect on employee performance and job satisfaction, as well as being the most dominant factor in improving performance. Motivation had a positive and significant effect on job satisfaction, but did not directly affect performance. Meanwhile, competence did not significantly affect performance or job satisfaction. Job satisfaction also did not significantly affect performance and was unable to mediate the relationship between variables. These findings indicate that employee performance in public service organizations is more determined by work behavior, especially discipline, than technical abilities or psychological factors.